Systemic inflammatory indices as a non-invasive grading modality for endometriosis: a comparative study versus exploratory laparoscopy - Ahmed Sabra Ibrahim Mohammed Sabra; Shreen Naguib Aboelezz Moselhy; Ahmed Kasem Mohamed Zain Eldin (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Included evaluation of the possibility of using the systemic inflammatory indices for preoperative screening for the presence and severity of endometriosis (EM) in comparison to the findings of the exploratory laparoscopy Methods: 88 women with clinical manifestations suggestive of EM were evaluated clinically and by US and gave blood samples for estimation of serum cancer antigen-125 (CA125), platelet and total and differential leucocytic counts for calculation of inflammatory indices; the Systemic Immune-Inflammation index, the Systemic Inflammation Response Index (SIRI), the Neutrophil-Lymphocyte ratio (NLR), the Neutrophil-Monocyte ratio, the Neutrophil-Platelet ratio and the Platelet-Lymphocyte ratio. Then, patients were prepared to undergo laparoscopy for diagnosis and staging. Results: Laparoscopy detected EM lesions in 63 patients; 27 of stage I-II and 36 of stage III-IV. Positive laparoscopy showed significant relation with US grading, high serum CA125 levels, platelet and inflammatory cell counts and indices. Statistical analyses defined high SIRI and NLR as the significant predictors for positive laparoscopy and high serum CA125 and NLR as the most significant predictors for severe EM (stage III-IV) on laparoscopy Conclusion: The intimate relation between EM and inflammation was reflected systematically as high levels of blood cellular components, but indices related to neutrophil especially NLR and SIRI showed highly significant relation to the presence and severity of EM and might be used as routine, cheap and non-invasive screening test before exploratory laparoscopy to guide the decision-making.